Memaksimalkan Keuntungan Dari Jasa dan Layanan di Bisnis Fotocopy Egy Kom Menggunakan Metode Simpleks - Chaniago, M. Fikri Al Hafiz; Syahputra, Egy Fahmi; Ubaidillah, Muhammad Sa’i; Rijal, Ahmad; Ritonga, Irmayanti (Journal of Computer Science and Information System(JCoInS), 2025)
Using the simplex method linear program operational research technique in the photocopy business is a smart strategy for optimizing business profits to become more efficient, by making better use of resources. In this article, we will discuss how to optimize service price profits, which is an important aspect in small and medium business management, especially in the field of printing services. This article discusses factors that influence the price profitability of photocopying services, including the cost of photocopying services. This research also explores customer interest in set prices. The method used involves a survey of photocopying service providers in certain areas, as well as data analysis of operational costs and commonly applied price structures. The results show that maximum competitive pricing benefits can be achieved with operational efficiency and a deep understanding of customer preferences. From the analysis carried out, it is proven that operational research techniques provide practical and easy to implement solutions. As a result, the photocopy business can be more competitive and survive amidst increasingly fierce competition